Clinical presentation and outcomes for adult ependymoma patients. Issue 3 (28th September 2016) - Acquaye, Alvina A.; Vera, Elizabeth; Gilbert, Mark R.; Armstrong, Terri S.
Abstract : BACKGROUND: Outcomes projects can be a catalyst for determining disease‐ and treatment‐related consequences for patients with rare tumors. The Adult Ependymoma Outcomes (AEO) survey uses self‐reported experience to evaluate how this tumor affects patient groups throughout the illness trajectory. METHODS: Patients completed the AEO survey via a Web‐based portal. The survey included questions on treatment, tumor recurrence, and current health status; the MD Anderson Symptom Inventory Brain Tumor and Spine Tumor modules; and the Medical Outcomes Study 36‐Item Short Form Health Survey (SF‐36). RESULTS: The sample included 264 participants (57% female) with a median age of 46 years (range, 18‐77 years). Radiation treatment was commonly used for patients who had brain involvement (χ 2 (1) = 20.7; P  < .001), underwent a partial resection (43%; χ 2 (3) = 15.4; P  < .001), or had a grade 3 tumor (41%; χ 2 (2) = 18.8; P  < .001). Recurrence occurred in a small group (29%), with grade 1 tumor patients 2.6 times more likely and grade 3 tumor patients 2.5 times more likely to experience recurrence than those with grade 2 tumors. Spine tumor patients had a higher symptom burden (mean, 2.8; scale, 0‐10) than brain tumor patients ( t (247) = −4.0), and they reported more moderate to severe symptoms (rating ≥ 5; 29%) than their counterparts (18%). Within the physical health portion of the SF‐36, spine tumor patients reported worse health with respect to bodily pain ( t (249) = 6.8; P  < .001), physical functioning ( t (252) = 4.1; P  < .001), and vitality ( t (202.2) = 3.0; P  < .003). CONCLUSIONS: These results demonstrate the feasibility of implementing outcomes projects that report on the clinical and demographic characteristics of a rare patient population, and they underscore the importance of outcomes data in understanding disease‐related issues. Cancer 2017;123:494–501. © 2016 American Cancer Society . Abstract : Implementing outcomes projects is feasible for ependymoma patients. Outcomes data help in understanding disease‐related issues for this patient population.